Dakwah Digital dan Tantangan Hukum Islam : Studi terhadap Narasi Keislaman di Platform Media Sosial - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Nabila Nurul Heptarina; Zulfa Rahma Putri Junovi; Jamiatun Niswah Nayli Muhammada (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The development of digital technology can change the way Islamic da'wah is conveyed, through social media platforms. Digital da'wah can make it easier to spread Islamic teachings more widely, in depth and easily accessed by various groups. However, behind this convenience, there are big challenges in aspects of Islamic law, especially related to the validity of information, ethics in preaching, and the potential for spreading teachings that are not in accordance with Islamic law. This research aims to examine the challenges of Islamic law in dealing with the digital da'wah phenomenon, especially in the spread of Islamic narratives on social media. The research method used is a literature study with a qualitative approach, which analyzes various literature related to Islamic law, ethics of da'wah, and the phenomenon of digital da'wah. The research results show that digital da'wah has great potential in spreading Islamic teachings, but also faces various challenges, such as a lack of supervision of Islamic content, the emergence of preachers without adequate knowledge, and the commercialization of da'wah which can obscure the essence of conveying Islam. Therefore, regulations and a deeper understanding of the principles of Islamic law are needed in preaching in the digital era so that da'wah.